High-energy electrical burn of the hand treated with skin grafting: case report. - Carrillo - Barraza , S., (Revista de Ciencias Médicas Torreón, 2026)
An electrical burn is a severe tissue injury that occurs whenan electric current flows through the body, turning it into aconductor and generating internal heat.This case report describes a 52-year-old male patientadmitted to the emergency department with an electrical burnand an Allman type III left clavicle fracture.A multidisciplinary approach and early rehabilitation areessential to optimize functional outcomes, reducecomplications, and preserve hand function, which is a keyfactor in the patient's quality of life.
Keywords: electrical burn, hand, skin graft